FABRICATION OF SINGLE PIECE HOLLOW BULB INTERIM OBTURATOR WITH PALATAL RAMP FOR TREATMENT OF HEMIMAXILLECTOMY AND HEMIMANDIBULECTOMY - A CASE REPORT - D., Anupama Prasad; D., Krishna Prasad; Hegde, Chethan (Journal of Health and Allied Sciences NU, 2013)
A male patient aged 45 years reported with squamous cell carcinoma of palate. Patient was seen presurgically and an immediate surgical obturator provided followed by an interim maxillary obturator by a novel method wherein hollowing the obturator bulb was planned which also had a palatal ramp to correct jaw relation lost due to hemimandibulectomy.The treatment was done in sequential order to correct the deviation of mandible to provide aesthetics to the subject and also for a comfortable social life with improved mastication and appearance.
Keywords: obturator; palatal ramp; maxillectomy; mandibulectomy; prosthodontic rehabilitation; aesthetic rehabilitation; functional efficiency; prosthesis